Peculiarities of Electrical Characteristics of Ferroelectric Memory Elements Based on PZT-Films; Russian Physics Journal; Vol. 58, iss. 9 - Delimova L. A.; Gushchina E. V.; Yuferev V. S.; Ratnikov V. V.; Zaitseva N. V.; Sharenkova N. V.; Seregin D. S.; Vorotilov K. A.; Sigov A. S. Aleksandr Sergeevich (2016, 2016)
Title screen